Cerebral hemometabolism: from isolated measurements to monitoring and therapy - Julio Cruz (Arquivos de Neuro-Psiquiatria)
An overview is presented on historical and multivariate aspects of cerebral hemometabolism. This involves a full multivariate approach, from blood pressure to cerebral metabolism. From isolated measurements, to monitoring and management, a comprehensive overview of cerebral hemometabolism is addressed, from its inception to current days, up to a new concept, the cerebral hemodynamic reserve. A multivariate functional diagram is proposed, to summarize the multivariate interrelationships of cerebral hemometabolism. A generic proposition is mode for studies of truly normal cerebral hemometabolism in children, for subsequent clinical applications. Another proposition is made for multivariate cerebral hemometabolic monitoring, in a broad variety of circumstances of predominantly global changes in intracranial dynamics, both in animal and clinical research.